6y-2x+5=0

Simple and best practice solution for 6y-2x+5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-2x+5=0 equation:


Simplifying
6y + -2x + 5 = 0

Reorder the terms:
5 + -2x + 6y = 0

Solving
5 + -2x + 6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -2x + -5 + 6y = 0 + -5

Reorder the terms:
5 + -5 + -2x + 6y = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -2x + 6y = 0 + -5
-2x + 6y = 0 + -5

Combine like terms: 0 + -5 = -5
-2x + 6y = -5

Add '-6y' to each side of the equation.
-2x + 6y + -6y = -5 + -6y

Combine like terms: 6y + -6y = 0
-2x + 0 = -5 + -6y
-2x = -5 + -6y

Divide each side by '-2'.
x = 2.5 + 3y

Simplifying
x = 2.5 + 3y

See similar equations:

| 4x-2(x-2)=-6+4x+2 | | 10h+25=90 | | 3/4n+7=10 | | -ab-3a^2b^2= | | 67654+98786= | | 187.92=6(007m+20.70+0.3(20.70)) | | 10x=56000-5000 | | 2x-40x=200 | | e^2x+1=10e^5x | | (X-2-5i)(x-2+5i)= | | 200.25=(x+7.90+4.90)15 | | -4x+2(x-3)=7x-12 | | U-7.1=6.11 | | 30+y=2y+15 | | X^2-98x+2392=0 | | 3(y+1)+2y=5(y-1+5) | | 0.3x=x-7 | | 6(6x-5)=22 | | 4xy=24 | | 13x-13=155+x | | -18-x=42+3x | | 5=13h | | Y=5.00+.40x | | 3(3x+6)=9x+18 | | 3x=20.5 | | -8x+x=27 | | -8.8(x-2.75)=17.6 | | -12x-8=21-11x | | (x/9)=-7x+8x-100-36 | | 1.2(x-3)+17.25=2.5x | | w=120p+185 | | 5x+28=(2)4x+5 |

Equations solver categories